The effects of plyometric training on athletic’ jump performance: a systematic review and meta-analysis - Ma, Shuzhen; Wang, Diliang; Soh, Kim Geok; Wang, Xinzhi; Xu, Yanqi; Tu, Qiang (Frontiers in Physiology, 2025)
BackgroundJump performance is essential in sports and relies on explosive power. Plyometric training (PT) specifically targets explosive power, while routine training (RT) focuses on general strength or sport-specific skills. Although many studies have shown that PT improves jump performance, few have directly compared PT and RT across different jump types. This study aims to address this gap.ObjectiveThis study compares the effectiveness of plyometric and regular training on enhancing jump performance in healthy athletes.MethodFive electronic databases (PubMed, ERIC, Web of Science, EBSCOhost, and Scopus) were comprehensively searched for relevant studies. Review Manager software was used for statistical analyses. The quality of included studies and risk of bias were assessed using the Cochrane Risk of Bias tool by two independent reviewers, with disagreements resolved by consensus. Forest plots and subgroup analyses were conducted for metrics with a sample size of three or more. Heterogeneity was assessed by using the I2 statistic (25% for low, 50% for moderate, and 75% for high). A random-effects model was used for high heterogeneity and a fixed-effects model for low heterogeneity. Estimates were reported with confidence intervals, and significance was set at α = 0.05.ResultsThe meta-analysis showed that plyometric training significantly improved counter movement jump performance compared to routine training (SMD = 1.99, 95% CI [1.50, 2.48], p < 0.001, I2 = 0%). For squat jump, there was no significant difference between the two training methods (SMD = 0.96, 95% CI [-0.10, 2.02], p = 0.07, I2 = 0%). Vertical jump performance also showed no significant difference (SMD = 2.90, 95% CI [-0.50, 6.30], p = 0.09, I2 = 63%). Subgroup analysis of vertical jump performance indicated low heterogeneity for female subjects (I2 = 0%) and high heterogeneity for male subjects (I2 = 71%), primarily due to the inclusion of one outlier study. Excluding this study reduced the heterogeneity to 5% (SMD = 3.20, 95% CI [1.80, 4.60], p < 0.001).ConclusionThis study shows that plyometric training significantly improves counter movement jump performance compared to routine training. However, there is no significant difference between the two training methods in squat jump and vertical jump performance. This study demonstrates that plyometric training significantly enhances counter movement jump performance, while showing no superior effects on squat jump and vertical jump performance compared with routine training.Systematic Review Registrationhttps://www.10.37766/inplasy2024.6.0107.